Effect of the Unilateral Breast Cancer Surgery on the Shoulder Movement: Electromyographic and Motion - Miguel-Andrés, Israel; García-González, Silvia Beatríz; Mayagoitia-Vázquez, José de Jesús; Barrera-Beltrán, Karla; Samayoa-Ochoa, Didier; León-Rodríguez, Miguel; García-García, Leonardo Azael (Revista Mexicana de Ingenieria Biomedica, 2022)
After breast cancer surgery, women might develop musculoskeletal impairments that affect movements of the upper limbs and reduce the quality of life. The objective of this research was to analyze the effect of the unilateral breast cancer surgery on the kinematics of the shoulder and the electrical activity of the upper trapezius, middle deltoid and pectoralis major muscles. Eight right-handed female participants, mean age 46.5 ± 5.45 years and mean body mass 71.21 ± 13.33 kg, with unilateral breast cancer surgery, without breast reconstruction and without lymphedema symptoms were included in the research. Flexion-extension and abduction-adduction movements of the shoulder were evaluated with infrared cameras and the electrical activity was measured using surface electromyography. The statistical analysis of the direction angles showed a significant reduction of the flexion-extension and abduction-adduction movements in the affected side in most of the participants (p<0.05). The muscle electrical activity did not present a significant difference between the two sides for the flexion-extension and abduction-adduction movements (p>0.05). The results suggest that the surgical procedure could compromise the range of motion of the affected side. Furthermore, this research contributes to clarify the effect of the surgical procedure in the range of motion of the upper limbs.